2019
DOI: 10.1111/gcb.14845
|View full text |Cite
|
Sign up to set email alerts
|

Gap‐filling approaches for eddy covariance methane fluxes: A comparison of three machine learning algorithms and a traditional method with principal component analysis

Abstract: Methane flux (FCH4) measurements using the eddy covariance technique have increased over the past decade. FCH4 measurements commonly include data gaps, as is the case with CO2 and energy fluxes. However, gap‐filling FCH4 data are more challenging than other fluxes due to its unique characteristics including multidriver dependency, variabilities across multiple timescales, nonstationarity, spatial heterogeneity of flux footprints, and lagged influence of biophysical drivers. Some researchers have applied a marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
120
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 77 publications
(150 reference statements)
2
120
0
1
Order By: Relevance
“…used another machine learning algorithm ANN to address the nonlinearity problem. Both random forest and ANN are capable of handling complex processes and overfitting issues, but the tree ensemble of random forest model can be interpreted more easily in comparison with the black box problem of ANN(Banerjee, Ding, & Noone, 2012) Kim et al (2020). found that random forest performed better than ANN in gap-filling F CH4 Tramontana et al (2016).…”
mentioning
confidence: 99%
“…used another machine learning algorithm ANN to address the nonlinearity problem. Both random forest and ANN are capable of handling complex processes and overfitting issues, but the tree ensemble of random forest model can be interpreted more easily in comparison with the black box problem of ANN(Banerjee, Ding, & Noone, 2012) Kim et al (2020). found that random forest performed better than ANN in gap-filling F CH4 Tramontana et al (2016).…”
mentioning
confidence: 99%
“…The cropland has been reported as carbon neutral to the atmosphere (e.g., Ciais et al, 2010), as a carbon source (e.g., Anthoni et al, 2004a;Verma et al, 2005;Kutsch et al, 2010;Wang et al, 2015;Eichelmann et al, 2016) and also as a carbon sink (e.g., Kutsch et al, 2010). Such inconsistency probably results from the different crop types and management practices (residue removal, the use of organic manure, etc.…”
Section: Comparison With Other Croplandsmentioning
confidence: 99%
“…Field management practices (e.g., irrigation, fertilization and residue removal, etc.) impact the cropland CO 2 fluxes (Baker and Griffis, 2005;Béziat et al, 2009;Ceschia et al, 2010;Eugster et al, 2010;Drewniak et al, 2015;de la Motte et al, 2016;Hunt et al, 2016;Vick et al, 2016), but their relative importance in determining the cropland CO 2 budget remain unclear because of limited field observations (Kutsch et al, 2010), motivating comprehensive CO 2 budget assessments across different cropland management styles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Peltola et al (2019) applied a Random Forest machine learning approach to upscaling eddy covariance CH 4 flux observations in northern wetlands using 500-to 1,000-m Moderate Resolution Imaging Spectroradiometer (MODIS) products, wetland maps, and other gridded data sets. Machine learning-based models have proven valuable in gap filling of eddy covariance CH 4 flux data (e.g., Dengel et al, 2013;Kim et al, 2020;Morin et al, 2017) and upscaling eddy covariance observations in northern wetlands (Peltola et al, 2019). However, machine learning models have been barely applied for upscaling point-based CH 4 flux measurements using relatively high-resolution Landsat products for local/regional emission mapping.…”
Section: Introductionmentioning
confidence: 99%